2021
DOI: 10.3390/cryst11020085
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Nanogenerator Based on Lead-Free Flexible PVDF-Barium Titanate Composite Films for Driving Low Power Electronics

Abstract: Self-powered sensor development is moving towards miniaturization and requires a suitable power source for its operation. The piezoelectric nanogenerator (PENG) is a potential candidate to act as a partial solution to suppress the burgeoning energy demand. The present work is focused on the development of the PENG based on flexible polymer-ceramic composite films. The X-ray spectra suggest that the BTO particles have tetragonal symmetry and the PVDF-BTO composite films (CF) have a mixed phase. The dielectric c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 33 publications
(34 reference statements)
0
34
0
1
Order By: Relevance
“…Sahu et al reported an output voltage of 7.2 V, current of 38 nA, and power density of 0.8 μW cm -2 from a PENG containing 10 wt% BaTiO 3 /PVDF composite film prepared by solvent casting. [277] The PENG was used to harvest energy from activities like finger tapping, dropping of coin and air blowing.…”
Section: Nanocomposites Based On Non-conducting Fillersmentioning
confidence: 99%
“…Sahu et al reported an output voltage of 7.2 V, current of 38 nA, and power density of 0.8 μW cm -2 from a PENG containing 10 wt% BaTiO 3 /PVDF composite film prepared by solvent casting. [277] The PENG was used to harvest energy from activities like finger tapping, dropping of coin and air blowing.…”
Section: Nanocomposites Based On Non-conducting Fillersmentioning
confidence: 99%
“…These hybrid materials have the virtues of low elastic moduli and significant piezoelectric properties, which could enable them to show attractive mechanical energy harvesting properties and accurate sensing abilities. Piezoelectric nanogenerators and sensors are two important types of functional electronic devices which have been extensively explored for inorganic perovskite materials, [17,18] such as BaTiO 3 , [19,20] CsPbBr 3 . [21,22] Very recently, the hybrid piezoelectric-based nanogenerators [16,[23][24][25][26] and human body motion sensors [27,28] have been reported and their excellent energy harvesting and sensing performance can be comparable to those of perovskite oxides.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, these devices can realize real-time transmission and analysis of motion without external battery, and the device size can be easily designed according to actual demand [ 36 , 37 , 38 ]. Due to mechanical flexibility, lightweight, high piezoelectric output and environmental protection, PVDF is always regarded as a candidate for Nanogenerators [ 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%